Cluzobra matilei sp. n. from French Guyana, with notes on congeners (Diptera: Mycetophilidae) - Kurina, Olavi (Zootaxa, 2008)
Five Cluzobra Edwards species were recorded from the Kaw Mountains in French Guyana. Cluzobra matilei sp. n. is described, with colour photographs and line drawings. The new species is compared with the closely related species C. variegata and C. vicina.